Synthesis of Fe3O4@TiO2 core-shell structure for effective particle-fluid separation after photocatalytic process - Ng, Che Tean (2014)
The usage of TiO2 photocatalysts inside liquid medium is facing a great challenge on difficulty and cost inefficient to be collected and reused by micro- or nano-filtration. Aiming to solve some disadvantages of TiO2 photocatalyst, a facile and effective synthesis method has been successfully developed to produce Fe3O4@TiO2 Core-Shell structure with magnetic Fe3O4 as cores and anatase TiO2 as shells. Firstly, the magnetite core nanoparticles were synthesized via low temperature oxidative hydrolysis method. During synthesis, the Fe3O4 colloidal dispersion was stabilized by a surfactant called Cetyl trimethylammonium bromide (CTAB), which serves to control the particle size and enhance the particle dispersion. On the synthesized Fe3O4 particles, a layer of TiO2 was in-situ formed, followed by heat treatment at three different temperatures to form the Fe3O4@TiO2 core-shell microspheres.